Pengaruh two stay three stray terhadap kecerdasan linguistik siswa Sekolah Dasar - Arief Rahman Hakim; Andika Gutama (Universitas Kanjuruhan Malang, 2020)
Abstract A good learning process must be able to make students become excited and play an active role. Thepurpose of this study was to determine the effect of the Two Stay Three Stray learning model onstudents' linguistic intelligence. This research is a quasy experimental study with a sample of 50fourth grade students of SDN Lumbang II, Lumbang District, Probolinggo Regency. Theinstruments used were observation and questionnaire. The data analysis technique used independentsample t-test. Hypothesis test results obtained significance value of 0.044 and Ha accepted. Basedon the results of the study note that there is a significant influence between the Two Stay Three StrayStray learning model on students' linguistic intelligence. Abstrak Proses pembelajaran yang baik harus mampu membuat siswa menjadi bersemangat dan berperan aktif. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh model pembelajaran Two Stay Three Stray terhadap kecerdasan linguistik siswa. Penelitian ini merupakan penelitian kuantitatif quasy eksperimen dengan sampel 50 siswa kelas IV SDN Lumbang II Kecamatan Lumbang Kabupaten Probolinggo. Instrumen yang digunakan adalah observasi dan angket. Teknik analisis data menggunakan independent Sample t-test. Hasil uji hipotesis diperoleh nilai signifikasi sebesar 0,044 dan Ha diterima. Berdasarkan hasil penelitian diketahui bahwa ada pengaruh signifikan antara model pembelajaran Two Stay Three Stray Stray terhadap kecerdasan linguistik siswa